The growth of carbon markets in Asia: The potential challenges for future development - Yukun Shi; Sudharshan Reddy Paramati; Xiaohang Ren (Asian Development Bank Institute (ADBI), 2019)
This paper is designed to provide comprehensive details on the carbon markets across the major Asian economies and with specific attention to the Chinese carbon market. We particularly discuss the carbon markets across the major northeast (the People's Republic of China [PRC], Japan, and the Republic of Korea) Asian economies. Further, we empirically explore the interrelationship between the Shanghai and Shenzhen carbon emission markets, using an autoregressive distributed lag (ARDL) model with daily high-frequency data from 3 January 2017 to 9 October 2018. The evidence from the analysis confirms unidirectional influence from the Shanghai carbon emission market on the Shenzhen carbon emission market. Our findings shed light on the carbon emission markets' policy formulation for the Chinese government to achieve sustainable economic growth and meet carbon reduction targets in the PRC. Finally, we provide numerous policy and practical implications for the Asian economies with respect to the issues of climate change policies.
Keywords: D53; O21; Q38; Q51; Q56; R11; 330; carbon emission markets; ARDL model; interrelationship; People's Republic of China